2016
DOI: 10.1039/c6nr03960j
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size scaling in silver nanowire films: design considerations for practical devices

Abstract: We report the first application of finite-size scaling theory to nanostructured percolating networks, using silver nanowire (AgNW) films as a model system for experiment and simulation. AgNWs have been shown to be a prime candidate for replacing Indium Tin Oxide (ITO) in applications such as capacitive touch sensing. While their performance as large area films is well-studied, the production of working devices involves patterning of the films to produce isolated electrode structures, which exhibit finite-size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In each case the presence of surface layers—molecules, surfactants, polymers, and native oxides—essential to stabilize these materials during synthesis and processing, represent barriers to physical integration and electrical connectivity. Thermal, mechanical and chemical processes have been employed to minimize these barriers and develop various applications based on metal nanowire networks (NWN) 1 , 2 , including flexible and transparent conductors 3 10 , energy storage 11 , 12 and generator devices 13 15 , sensors and memory devices 16 , 17 . Nanoscale dielectric layers give rise to material-independent ubiquitous behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In each case the presence of surface layers—molecules, surfactants, polymers, and native oxides—essential to stabilize these materials during synthesis and processing, represent barriers to physical integration and electrical connectivity. Thermal, mechanical and chemical processes have been employed to minimize these barriers and develop various applications based on metal nanowire networks (NWN) 1 , 2 , including flexible and transparent conductors 3 10 , energy storage 11 , 12 and generator devices 13 15 , sensors and memory devices 16 , 17 . Nanoscale dielectric layers give rise to material-independent ubiquitous behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This can be very beneficial for a more realistic prediction of the performances of any network, with the final goal of optimizing them. In parallel, Large et al used finite-size scaling theory to investigate AgNW networks for both experimental and simulation purposes [ 70 ]. This approach appears to be very pertinent since instead of considering the properties of MNW networks as homogeneous large area films, some applications (such as capacitive touch sensors) require device patterning.…”
Section: Modelling Of Mnw Network: a Brief Surveymentioning
confidence: 99%
“…This approach appears to be very pertinent since instead of considering the properties of MNW networks as homogeneous large area films, some applications (such as capacitive touch sensors) require device patterning. Large et al used the finite-size scaling theory to investigate the influence of the variation of the MNW length distribution on the properties of the network [ 70 ]. This approach could have direct implications towards choosing the appropriate MNW nature and dimensions for a more efficient integration within industrial applications that require device patterning.…”
Section: Modelling Of Mnw Network: a Brief Surveymentioning
confidence: 99%
“…3,4,8,9 There are secondary benefits as well, including low-temperature solution processing methods, [10][11][12] low-energy patterning techniques, 2,5,13 and compatibility with existing device architectures. 14,15 This combination of properties make AgNWs an attractive material for the electronics industry.…”
Section: Introductionmentioning
confidence: 99%
“…Utilising the percolation simulation framework described in 2,14 and detailed in, we can determine the junction density of a film of nanowires at arbitrary sheet resistance. At the percolation threshold (where the largest reductions in R S are seen in the work of ) we find that the junction density for the nanowire material in the present study is approximately for both L-S deposited and stamped graphene-AgNW hybrids is shown in Figure 4d.…”
mentioning
confidence: 99%